Perbandingan Nilai Corrected Count Increment pasca transfusi Thrombocyte Concentratedengan Thrombocyte Apheresispada penderita Keganasan Hematologi - Like Rahayu Nindhita; Dian Widyaningrum (Medica Hospitalia : Journal of Clinical Medicine, 2019)
Introduction : Transfusion thrombocyte concentrate (TC) and thrombocyteapheresis (TA) is a form of use of blood components as supportive measures to increase the number of platelets of patients with hematological malignancies thrombocytopenia, platelet transfusion success rated the corrected count increment (CCI).1 Platelet transfusion refractoriness (PTR) or failure increase in platelet post platelet transfusion, defined as more than two times the transfusion episode or successively obtained the value CCI <7.5 at 1 hour post first transfusion or <4.5 at 18-24 hours post transfusion.31 Materials and methods : Research samples from hematologic malignancies patients with platelet counts <50,000 / mm3, enforced through inspection Bone Marrow punction (BMP), got 2 or more episodes of platelet transfusions in the form Thrombocyte Concentrate (TC) and Thrombocyte Apheresis (TA), aged 1-70 years, do a complete blood count, is hospitalized at Dr. Kariadi’s hospital Semarang during the study period, from the number of pre- and post platelet transfusion CCI value is then determined between the recipient TA and TC. CCI value between TA to TC compared to perform statistical analysis computer using Mann Whitney test Research result : A study of 82 patients with both men and women diagnosed with Hematologic Malignancies obtained Platelet refractoriness cases as much as 5 of the 41 patients who received a transfusion history of using TA (12.19%), and 30 of 41 patients who received a transfusion history using TC (73.17 %). Mann Whitney test showed the value of CCI in case the recipient PTR between TA and TC got significant differences (p <0.05). Conclusion : There is significant difference between the value CCI of TA resipients and TC resipients. The value CCI of TA recipient was significantly higher than the value CCIof TC recipients. Keywords : thrombocyte apheresis, thrombocyte concentrate, CCI, PTR Pendahuluan: Transfusi thrombocyte concentrate (TC) dan thrombocyteapheresis (TA)merupakan bentuk penggunaankomponen darah sebagai tindakan suportif untuk meningkatkan jumlah trombositpasien keganasan hematologi dengan trombositopenia, Keberhasilan transfusi trombositdinilai dengan corrected count increment(CCI).1Platelet transfusion refractoriness (PTR) atau kegagalan kenaikan trombosit post transfusi trombosit, didefinisikan sebagai lebih dari dua kali episode transfusi atau berturut-turut didapatkan nilai CCI < 7,5 pada 1 jam pertama post transfusi atau < 4,5 pada 18-24 jam post transfusi.31 Bahan dan metode: Sampel penelitian adalah penderita keganasan hematologidengan jumlah trombosit <50.000 /mm3, ditegakkan melalui pemeriksaan Bone Marrow Punction (BMP), mendapat 2 atau lebih episode transfusi trombosit berupa Thrombocyte Concentrate (TC) maupunThrombocyte Apheresis (TA), usia 1-70 tahun, dilakukan pemeriksaan darah lengkap, menjalani rawat inap di RSUP Dr. Kariadi Semarang selama periode penelitian, Dari jumlah trombosit pre dan post transfusi kemudian ditentukan nilai CCI antara resipien TA dan TC. Nilai CCI antara TA dengan TC dibandingkan dengan melakukan analisis statistik komputer menggunakan uji Mann Whitney Hasil penelitian: Penelitian terhadap 82 pasien laki-laki maupun perempuan dengan diagnosis Keganasan Hematologi didapatkan kasus Platelet refractoriness sebanyak 5 dari 41 pasien yang mendapatkan riwayat transfusi menggunakan TA (12,19%), dan 30 dari 41 pasien yang mendapatkan riwayat transfusi menggunakan TC (73,17%).Uji Mann Whitney menunjukkan nilai CCI pada kasus PTR antara resipien TA dan TC didapatkan perbedaan secara signifikan (p<0,05). Simpulan: Didapatkan perbedaan secara signifikan nilai CCI antara yang mendapatkan TA dan yang mendapatkan TC. Nilai CCI resipien TA secara bermakna lebih tinggi daripada nilai CCI resipien TC Kata kunci :thrombocyte apheresis, thrombocyte concentrate, CCI, PTR